THE EFFECT OF SALT SPRAYING ON THE HATCHABILITY PERFORMANCE OF THE HYBRID DUCK EGGS - R. A., Sutiyo; Wirapartha, M.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2020)
This research hass been done in Mr. Budiono house which stay in Sidorejo Village, Rowokangkung District, Lumajang City, and this research in 1,5 mounth. This research progam is used Completely Randomized Design (CRD) with 4 treatment and 4 repetition and the contained in every repetition is 15 egg duck. P0 treatment as control (duck egg sprayed with warm water 38 o C), P1 (salt solution with dose 10 g/liter warm water 38 o C), P2 (salt solution with dose 20 g/liter warm water 38 o C), P3 (salt solution with dose 30 g/liter warm water 38 o C).  The variable observed is egg weight, eeg indexs, fertility, egg shrinkage, DOD weight, mortality and hatchability. The result of research indicate the influence of spraying hybrid duck eeg with salt water to P0, P1 treatment and P3 not diffirent obvious (P>0,05) toward eeg weight, eeg index, fertility, eeg shrinkage and DOD weight but on P2 treatment real influence (P<0,05) toward mortality and hatchability. The conclusion of this research is influence of spraying hybrid egg duck with salt water on control consentration (P0), 10 g/liter warm water 38 o C (P1), and 30 g/liter warm water 38 o C (P3) hass not effect toward egg weight, egg index, fertility, shrinkage and DOD weight, but salt consentration 20 g/liter warm water 38 o C (P2) reduce embrio mortality during hatchability processed and increase egg hatchability. Keywords : hatchability, hatching machine, salt water spraying, duck egg